Research-practice partnerships for school improvement : the learning schools model - Lai, Mei Kuin; McNaughton, Stuart; Jesson, Rebecca; Wilson, Aaron (Bingley, U.K. : Emerald Publishing Limited, 2020)
There is an increasing focus on research-practice partnerships that adopt research designs aimed at improving educational practice while advancing research knowledge. There is now a need for books that provide a theoretical and practical account of successful research designs that have been tested and replicated over time and contexts. This book addresses this need by providing the first comprehensive account of the Learning Schools Model (LSM), a design-based research-practice partnership that has been tested over 15 years and across contexts and countries (n=5). This model has successfully built teacher and school capacity and improved valued student outcomes for primarily indigenous and ethnic minority students from lower socio-economic communities. The quality of research into the model has been recognised locally and internationally. The International Literacy Association reprinted a paper on the original model in their volume Theoretical models and processes of Reading (6th Ed). The authors won the University of Auckland's Research Excellence Award (2015), awarded for research of demonstrable quality and impact, for their research into the Model. This book addresses several gaps in the existing literature on research-practice partnerships. Firstly, understanding applications in contexts beyond the USA where much of the seminal work is located adds to our collective understanding of contexts in terms of constraints and enablers. Secondly, we provide a theoretical account of partnership development and demonstrate how these are practically developed in situ to address the known need for stronger theoretical understandings of partnership development and better training in developing partnerships. Finally, our book demonstrates how research can be both responsive to context and yet have robust and replicable research designs that improve valued student outcomes over time and contexts. This in turn provides an alternate research approach for countries where randomised control trials are often the gold standard for interventions.
Foreword -- Chapter 1 : Ambitious aims : research for solutions and knowledge -- Chapter 2 : The Learning Schools Model (LSM) -- Chapter 3 : Collaborative data analysis -- Chapter 4 : Partnerships for design and sustainability -- Chapter 5 : Resourcing and Professional Learning and Development (PLD) -- Chapter 6 : Sustainability of the LSM -- Chapter 7 : Learning to learn -- References -- Index.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: School improvement programs; Educational change; Educational productivity; Minorities -- Education; Indigenous peoples -- Education; Education -- Administration -- General; Curriculum planning & development